PENERAPAN PEMBELAJARAN MIND MAPPING DENGAN GAME POHON PENGETAHUAN UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR - Siti Sopiah (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2019)
This research is motivated by the results of observations known to students experiencing difficulty in achieving the minimum completeness target and the lack of active students in learning. The author solves this problem by applying the Mind Mapping model to the knowledge tree game. This study aims to improve the activity and student learning outcomes. Research in the form of Class Action consisting of 2 cycles, each cycle consisting of 2 meetings with four stages, namely: planning, action, observation and reflection. The research subjects were students of class VIII-B MTsN 4 Pangandaran. Data to be taken include: student activity data, learning outcome data, teacher performance data during learning and student response data. The results showed an increase in activeness and student learning outcomes from cycle I to cycle II. The percentage of students' activeness in cycles I and II respectively: 59.26% and 81.48% while the percentage of classical completeness in cycles I and II respectively: 81.48% and 96.23%. Teacher performance during learning has reached good criteria. Students give positive responses to learning. The results of the study concluded that the application of Mind Mapping with the knowledge tree game could increase student learning activities and outcomes in the Structure and Function of Plant Network Functions in class VIII-B MTsN 4 Pangandaran. Learning with this model can be used to improve student activity and learning outcomes.